Population Ageing in New Zealand: The Impact on Living Standards and the Optimal Rate of Saving with a Flexible Real Exchange Rate - Ross Guest; Grant Scobie; John Bryant (New Zealand Government, The Treasury, 2003)
The purpose of this paper is to extend the simulation analysis of population ageing in Guest, Bryant and Scobie (2003). In that paper a single-good Ramsey-Solow model was calibrated for New Zealand and used to simulate the impact of population ageing on optimal national saving and average living standards over the next 100 years. There are several innovations in the present paper. One is to allow for tradable and non-tradable goods and thereby to introduce a real exchange rate. Changes in the real exchange rate due to population ageing produce substitution effects between tradable and non-tradable goods, in both consumption and investment. Other innovations in this paper are an outward-looking model of utility, a proportion of rule-of-thumb consumers, and a vintage capital model. The simulations of population ageing are conducted by first deriving a range of demographic projections from alternative assumptions about fertility, mortality and immigration. The resulting series for population and employment by age group are weighted to account for age-specific labour productivity levels and consumption demands. The model is solved by finding optimal paths of investment and consumption from an initial steady state to a new steady state following a demographic shock. The sanguine assessment of the impact of population ageing on living standards and national saving in Guest, Bryant and Scobie (2003) remains intact following the extensions applied to the model in this paper. That is, the cost of ageing is equivalent in its effect on living standards to an annual loss of labour productivity growth of about a quarter of one percent over the next 50 years. The optimal path for national saving implies a rise of up to 2% of GDP over the next decade, relative to that which would have been optimal in the absence of population ageing. In all the cases considered, the optimal level of savings then trends down, so that by 2051 it would be about 2 percentage points of GDP lower than the level that would have been optimal were the population age structure to have remained unchanged.
Keywords: E21; E22; F20; F21; 330; consumption; saving; inter-temporal paths; Ramsey model; population ageing; foreign exchange; New Zealand